Clinical Features and Outcomes of Pasteurella multocida Infection. Issue 36 (September 2015) - Giordano, Antonio; Dincman, Toros; Clyburn, Benjamin E.; Steed, Lisa L.; Rockey, Don C.; Barbara, Adamik.
<x xml:space="preserve">Abstract</x> Abstract Pasteurella multocida, a zoonotic infectious organism, has most often been described in patients after an animal bite. Here, we characterize the clinical features and outcomes of P multocida infection in a large cohort of patients according to the presence or absence of an animal bite. We retrospectively searched MUSC's laboratory information system for all patients with positive P multocida cultures from 2000 to 2014. Extensive data were abstracted, including clinical and outcome data. The Charlson comorbidity index (CCI) was used to assess comorbidities among patients. We identified 44 patients with P multocida infections, including 25 with an animal bite. The average age was 64 years and the majority of patients were women (N = 30). There was no difference in age and sex distribution among those with and without a bite (P = 0.38 and 0.75, respectively). A CCI ≥1 was significantly associated with the absence of a bite (P = 0.006). Patients presenting without a bite were more frequently bacteremic (37% vs 4%, respectively, P = 0.001), and were hospitalized more often (84% vs 44%, respectively, P = 0.012). Of the 8 patients who required intensive care unit (ICU)-based care, 7 were non-bite-related. There were 4 deaths, all occurring in patients not bitten. P multocida infections not associated with an animal bite were often associated with bacteremia, severe comorbidity(ies), immune-incompetent states, the need for ICU management, and were associated with substantial mortality.